The Integration of Technology in Early Childhood Education: An Investigation of Teachers' Perceptions of Its Implementation and Impact - Hasanah, Nor Izzatil; Aziza, Aspiya; Azizah, Nor; Selvia (Proceeding International Conference on Education, 2024)
The perception of educators regarding the significance of integrating technology in early childhood learning exerts a considerable influence on the manner in which technology is integrated into learning at early childhood education. Accordingly, the objective of this research is to elucidate the perceptions of early childhood teachers in Banjarmasin with regard to the integration of technology in learning. this research employs a mixed-methods approach. The data was collected through closed and open questionnaires to a sample of 232 teachers. Subsequently, the data was subjected to descriptive and thematic analysis. The findings of this research demonstrate that the findings of the research indicate that the majority of early childhood teachers in Banjarmasin perceive the integration of technology to be of significant importance. It is perceived that the integration of technology offers a range of benefits for teacher’s perception delivery and evaluation of learning. It is believed that technological advancements can assist in developing children's learning styles, facilitate their learning processes and enhance their enthusiasm for learning. Additionally, technology can foster teacher professionalism in the classroom. However, concerns regarding the suitability of technology for children's age and development, the potential negative impact of technology on children's development, teacher competence and the limited facilities in paud institutions present significant challenges.